2019
DOI: 10.1002/jsfa.10185
|View full text |Cite
|
Sign up to set email alerts
|

Changes in oxalate composition and other nutritive traits in root tubers and shoots of sweet potato (Ipomoea batatas L. [Lam.]) under water stress

Abstract: BACKGROUND: The presence of insoluble calcium oxalate druse crystals (CaOx) in sweet potato (Ipomoea batatas) can negatively affect its nutritional quality. Photosynthesis, starch, and protein composition are linked with oxalate synthesis and tuber quality under water scarcity. Our main objective was the oxalate quantitation of sweet potato tubers and shoots and also to assess how drought changes their nutritional value. Eight sweet potato accessions from Madeira, the Canaries and Guinea-Bissau were analyzed f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 36 publications
(107 reference statements)
1
11
0
Order By: Relevance
“…It still allowed good photosynthesis activity and avoided the starch degradation into sugars, reducing its mobilization into tubers. However, in such conditions, the carbohydrate metabolism and photosynthesis oxidative processes can produce oxalic acid, forming insoluble salts when combined with free calcium, as CaOx insoluble druse crystals [61]. We observed that the whole-plant CaOx average content decreased in the first trial, with an increase in the second trial.…”
Section: Sweet Potatomentioning
confidence: 63%
“…It still allowed good photosynthesis activity and avoided the starch degradation into sugars, reducing its mobilization into tubers. However, in such conditions, the carbohydrate metabolism and photosynthesis oxidative processes can produce oxalic acid, forming insoluble salts when combined with free calcium, as CaOx insoluble druse crystals [61]. We observed that the whole-plant CaOx average content decreased in the first trial, with an increase in the second trial.…”
Section: Sweet Potatomentioning
confidence: 63%
“…OA was quantitated in flour samples from root tubers and shoots (Gouveia et al 2020). Exactly 0.4 g of flour was extracted with hydrochloric acid (HCl, 6.0 M) to allow the reduction of oxalic into glyoxylic acid, with a further reduction into glycolic acid.…”
Section: Methodsmentioning
confidence: 99%
“…WUE reflects how plants manage the water use for vital activities and plant production during scarcity conditions, with the most tolerant ones usually displaying higher WUE (Mengel et al 2001, Ganança et al 2018, Gouveia et al 2019). The chlorophyll measured in the full‐grown leaves could be associated with the rate of photosynthesis, which is one of the most common parameters used as indicator of plant performance under drought stress (Shao et al 2015, Salehi‐Lisar and Bakhshayeshan‐Agdam 2016, Gouveia et al 2020). The carbon isotopic discrimination (Δ 13 C), that represents the photosynthetic depletion of 13 C in field‐grown plants, is linked with stomatal aperture and is commonly used in C3 plants for the assessment of drought resilience (Farquhar et al 1989, Zhang et al 2015, Gouveia et al 2019).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations